Analysis of production cost calculation using full costing method on selling price of Sogistudio MSMEs in Pasuruan - Haliza, Sabrina Ainur; Nurrahma, Ilfi; Afdhillah, Nur Aini; Chilmi, Hanum Roudhotul; Fahriani, Dian (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
Cost of goods manufactured (COGS) is the direct and indirect costs incurred to improve an item so that it can be sold. Before determining the selling price, it is necessary to calculate the cost of goods produced. This descriptive qualitative research uses interview methods and literature studies to collect, analyze, and interpret data to obtain a deep understanding. This study aims to determine the importance of calculating the cost of production of t-shirt products at the Nobashi shrimp factory in Sogi Studio MSMEs using the full costing method. this research uses the full costing method analysis tool, where the definition of the full costing method is a method of determining the cost of production to take into account all elements of production costs into the cost of goods manufactured. The results of this study indicate that Sogi Studio MSMEs have made accurate calculations. Researchers classify production costs into three categories: raw material costs, direct labor costs, and factory overhead costs, which can be both variable and fixed costs